Bimetallic docked covalent organic frameworks with high catalytic performance towards tandem reactions. Issue 44 (15th April 2016) - Leng, Wenguang; Ge, Rile; Dong, Bin; Wang, Chang; Gao, Yanan
Abstract : Mn/Pd bimetallic docked covalent organic frameworks showed high catalytic performance towards a tandem reaction. Abstract : Mn/Pd bimetallic docked covalent organic frameworks were fabricated via a programmed synthetic procedure. Within the framework, MnCl2 could only coordinate with the bipyridine ligands, while Pd(OAc)2 could occupy the rest of the nitrogen sites. Such bimetallic docked materials showed high catalytic activity in a Heck-epoxidation tandem reaction.